Pendidikan Kesehatan Dalam Upaya Untuk Mengubah Sikap Dan Perilaku Dan Implementasi Pemeriksaan Kesehatan Gigi - Mulut Pada Ibu Hamil - Nurhaedah, Nurhaedah; Treasa, Adisty Dwi; Anggraini, Arie; Rahmawati, Eka; Hikmah, Mutiara; Latif, Farida; Rosmiati, Rosmiati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Brushing teeth properly is brushing teeth that is done using a method that can clean the entire surface of the teeth without injuring the soft tissue in the mouth and is done sequentially from one side to the other regularly. Therefore, dental and oral health is something that needs to be considered by pregnant women. The purpose of this study was to analyze dental and oral health education services for pregnant women. The method of implementing activities is carried out with health education in an effort to change attitudes and behaviors and the implementation of dental and oral health checks in pregnant women. The results of community service activities are providing dental and oral health education by brushing teeth properly as a concrete effort in implementing a healthy life by maintaining dental and oral health is important to do. Intervention solutions to overcome dental caries are by providing health education with dental and oral hygiene facilities, as well as monitoring so that the implementation of the health behavior model as health education can run well. The conclusion is that the actions to maintain dental and oral health of pregnant women are mostly in the good category. Dental and oral health maintenance actions are things that are carried out by respondents related to disease prevention.